P162 THE GENE EXPRESSION LANDSCAPE OF COBBLESTONE LESIONS IN CROHN'S DISEASE-LIKE ILEITIS. (18th January 2018) - Rodriguez-Palacios, Alexander; Huang, Lihua; Cominelli, Fabio
Abstract: Background: We recently described cobblestone (Cob) lesions in the ileum of SAMP1/YitFc (SAMP) mice, which is the only inbred mouse strain with polygenic predisposition to Crohn's disease(CD)-like ileitis. Herein, we quantified the mRNA gene expression differences across microscopically dissected samples from ileal tissues of adult germ-free (GF)-SAMP mice. Methods: Twelve adult GF-SAMP mice (40–55 wks) divided into two groups, were maintained as GF, or colonized with the gut microbiome of a newly diagnosed CD patient. A novel 3D-stereomicroscopic pattern profiling strategy was used to harvest, after 22 days of colonization, 9–10 tissues associated with Cob structures and lymphoid tissues in each mouse. Following RNA extraction, we mapped and quantified the mRNA transcriptomic differences across samples. Results: In total, 91 samples with 1.17 billion informative reads (20, 942 genes) showed that within SAMP larger genetic differences occurred at the center of Cob lesions due to prominent oxidative stress. Controlling for disease severity, analysis of gut lymphoid tissues exhibiting mild disease showed overexpression of 51 genes clustered within the defensin/antimicrobial (enrichment score, ES4.73), and fatty acid binding pathways (ES2.55). Significant down-regulation of 107 genes was due to extracellular and disulfide bond (ES19.25), peptidase S1 (ES9.76), and fat metabolism (ES3.32) pathways. When Cob data was examined for colonized mice, 1751 genes exhibited abnormal function in severely inflamed mice with only 30 up-regulated (disulfide bond, cellular response to IL-1, defense response; histone core) but 1722 down-regulated (metal-binding; defensin) genes. Several miRNA genes were also abnormal. Conclusion: Multi-sample RNA-seq analysis in GF-SAMP mice indicate that Cob severity could be due to excessive activation of disulfide bond, cellular response to IL-1, and defense responses, among other abnormalities (e.g., miRNA overexpression), in severe Cob ileitis.